2017
DOI: 10.4103/ijmr.ijmr_1581_16
|View full text |Cite
|
Sign up to set email alerts
|

Incidence & prognosis of acute kidney injury in individuals of snakebite in a tertiary care hospital in India

Abstract: Background & objectives:The snakebites are considered to be an occupational hazard in agriculture workers and the snake handlers, resulting in a considerable morbidity, mortality and economical implications. This study was conducted to determine the incidence, clinical presentation, renal injury and clinical outcome in snakebite victims who developed acute kidney injury (AKI).Methods:This hospital-based prospective, observational study was done on 100 cases who were admitted for the management of snakebite and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…Systolic blood pressure (BP) was <120 mm Hg in 68 and BP was not recordable in four patients. 18 In the present study, 14 out of 56 patients (25%) developed AKI and 11 out of 14 patients (78.5%) who had AKI required haemodialysis. These results were similar to the results reported by Jayakrishnanan M P et al which showed occurrence of AKI in 25% patients.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Systolic blood pressure (BP) was <120 mm Hg in 68 and BP was not recordable in four patients. 18 In the present study, 14 out of 56 patients (25%) developed AKI and 11 out of 14 patients (78.5%) who had AKI required haemodialysis. These results were similar to the results reported by Jayakrishnanan M P et al which showed occurrence of AKI in 25% patients.…”
Section: Discussionsupporting
confidence: 45%
“…Pulimaddi R found similar trend in reporting to hospital where 86 out of 100 patients arrived in the hospital within 24h, and 14 arrived after 24h. 18 The main examination findings in the present study were local rise in temperature, local tenderness, lymph node enlargement, swelling crossing proximal joint, compartmental syndrome, cellulitis and necrosis. Various neurotoxic signs were ptosis, ophthalmoplegia and dysphagia.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…One of the main issues in regard to snakebite-induced AKI is that after an apparent recovery in victims, it may progress to CKD. There are very few studies that monitored snakebite-induced AKI among the victims over longer periods of time to evaluate the risk of AKI progressing to CKD [28,[43][44][45]. The inherent limitations of these studies include a lack of information on renal function of patients prior to their envenoming incident, the identity of the perpetrating snake species, standardized follow-up programs, standardized methods for determining the severity of initial kidney injury, and differences in interventions made during the acute phase of envenoming.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that the combination of inflammatory and hemorrhagic syndromes impacted kidney function also in some non AKI patients. Clinical hemorrhages, uncoagulable blood, reduced hemoglobin, hyperleukocytosis and/or thrombocytopenia were observed during AKI (Table 3) and were generally significantly higher in AKI patients [20,45,50,[52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%